Wool : science and technology - Simpson, W. S.; Crawshaw, G. H. (Woodhead Publishing Limited series on fibres., 2002)
In this groundbreaking book, leading experts within the industry come together to give the first comprehensive treatment of the science and technology of wool to be published in over 20 years. Wool: Science and technology covers all aspects of the modern wool industry from raw material to finished product and is an essential reference resource for anyone involved in the worldwide wool industry whether as processor, manufacturer, or user for the garment and carpet trades.